2017
DOI: 10.1155/2017/4598314
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Female Acute Urinary Retention Presenting to the ED

Abstract: Introduction Acute urinary retention is a rare occurrence in women necessitating further investigation. Potential underlying causes may be broadly classified into obstructive, neurological, pharmacological, and psychogenic categories. Case A 36-year-old nulliparous female presented to the Emergency Department with a two-day history of acute urinary retention. Point-of-care ultrasonography and CT scan imaging confirmed the presence of a large uterine mass causing compression of the bladder. The acute retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Also, neurological impairment can cause or exacerbate urinary retention by interrupting the sensory and/or motor innervation of the detrusor muscle 4 . Furthermore, diabetes mellitus can also contribute to AUR due to neuropathy developed from myogenic and neurogenic alterations as a result of prolonged hyperglycemia and production of oxidative stress products 10–13 . In our study, we also similarly found that the rates of AUR occurrence were higher in patients with diabetes and neurological diseases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Also, neurological impairment can cause or exacerbate urinary retention by interrupting the sensory and/or motor innervation of the detrusor muscle 4 . Furthermore, diabetes mellitus can also contribute to AUR due to neuropathy developed from myogenic and neurogenic alterations as a result of prolonged hyperglycemia and production of oxidative stress products 10–13 . In our study, we also similarly found that the rates of AUR occurrence were higher in patients with diabetes and neurological diseases.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of AUR in BPH patients also increases in patients with comorbid conditions such as diabetes and neurological diseases 10–13 . The pathophysiology of BPH in patients with diabetes could possibly be explained by an increased sympathetic tone and stimulation of prostate growth by insulin 14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, AUR as a consequence of neurological etiologies can also be painless, such as those caused by acute spinal cord injury. The etiologies of AUR are myriad, ranging from obstructive, infectious, neurogenic, iatrogenic, and pharmacologic causes 2‐7 . AUR can happen in any population, however, its incidence in males is more than 10‐fold higher than in women, particularly with increased aging.…”
Section: Introductionmentioning
confidence: 99%
“…The etiologies of AUR are myriad, ranging from obstructive, infectious, neurogenic, iatrogenic, and pharmacologic causes. [2][3][4][5][6][7] AUR can happen in any population, however, its incidence in males is more than 10-fold higher than in women, particularly with increased aging. Indeed, studies indicate that benign prostatic hypertrophy (BPH) is the leading cause of AUR in male which accounts for more than 50% of all cases.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology is related to the mechanical compression of proximal urethra by the incarcerated fibroid and urethral elongation, resulting in intermittent voiding dysfunction. 5 …”
Section: Discussionmentioning
confidence: 99%